1996
DOI: 10.1161/01.cir.93.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Folate Status, a Common Mutation in Methylenetetrahydrofolate Reductase, and Plasma Homocysteine Concentrations

Abstract: Background Methylenetetrahydrofolate reductase (MTHFR) synthesizes 5-methyltetrahydrofolate, the major carbon donor in remethylation of homocysteine to methionine. A common MTHFR mutation, an alanine-to-valine substitution, renders the enzyme thermolabile and may cause elevated plasma levels of the amino acid homocysteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
757
16
23

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,297 publications
(834 citation statements)
references
References 8 publications
38
757
16
23
Order By: Relevance
“…The finding of an interaction effect between smoking and MTHFR(C677T) genotype has not been reported previously. A suboptimal plasma folate status among smokers (Piyathilake et al, 1994;Cafolla et al, 2000;O'Callaghan et al, 2002) might explain the observed interaction, as plasma folate has been shown to interact with MTHFR(C677T) genotype (Jacques et al, 1996b;Brattstrom et al, 1998;Girelli et al, 1998;McQuillan et al, 1999;Dekou et al, 2001;Saw et al, 2001). The involvement of folate is further supported by another study in which smoking was reported to interact with the dietary intake of folate (De Bree et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding of an interaction effect between smoking and MTHFR(C677T) genotype has not been reported previously. A suboptimal plasma folate status among smokers (Piyathilake et al, 1994;Cafolla et al, 2000;O'Callaghan et al, 2002) might explain the observed interaction, as plasma folate has been shown to interact with MTHFR(C677T) genotype (Jacques et al, 1996b;Brattstrom et al, 1998;Girelli et al, 1998;McQuillan et al, 1999;Dekou et al, 2001;Saw et al, 2001). The involvement of folate is further supported by another study in which smoking was reported to interact with the dietary intake of folate (De Bree et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that B-vitamin status is a major determinant of tHcy in the general population (Jacques et al, 1996b(Jacques et al, , 2002Hustad et al, 2000;Moat et al, 2003). Little attention has been given to the effect of overall dietary pattern regarding tHcy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTHFR 677TT genotype confers a significant risk of hyperhomocysteinemia that is most pronounced in individuals with low folate [15,16] or low riboflavin [17] status. Interestingly, the MTHFR 677C>T polymorphism appears to have a sex-specific effect on homocysteine [18].…”
Section: Introductionmentioning
confidence: 99%
“…7 Homozygous MTHFR C677T mutations can cause mildly elevated homocysteine levels, but this effect is neutralised if there is a high folate content in the diet. 8 Thus, many patients homozygous for this abnormality have normal homocysteine levels. In contrast, most studies directly measuring homocysteine find high levels to be associated with RVO.…”
Section: Introductionmentioning
confidence: 99%